Systematic Literatur Review: Peran Digital Marketing dalam Membangun Kepercayaan Konsumen pada Industri Insurtech - Noor, Zulki Zulkifli (Postgraduate of Jayabaya University, 2026)
Insurtech has shifted insurance interactions from face to face meetings to digital screens, creating significant challenges in building consumer trust without human touch. This study aims to evaluate the effectiveness of friendly chatbots versus in app cost transparency in shaping customer confidence. The method used is a Systematic Literature Review (SLR) with the PRISMA protocol, analyzing 12 reputable journal articles from 2020 to 2025. The results indicate that cost transparency plays a fundamental role in mitigating fraud risk perceptions and building initial integrity. Conversely, AI based chatbots serve as accelerators that provide privacy comfort due to their non judgmental nature, particularly in collecting sensitive data. In conclusion, effective digital marketing strategies should not choose one over the other but rather position transparency as the logical foundation and chatbots as an empathic interface. These findings contribute to Trust Commitment Theory by proposing a hybrid trust model for digital financial services.